Play in the early years - Owen, Kay (SAGE Publishing Ltd, 2021)
"Play in the Early Years offers students an accessible introduction to Play by considering key concepts and current debates in order to provide them with a strong foundation for their own research and practice. This textbook offers a theoretical underpinning and key debates, encouraging criticality within readers and helping them to connect theory with practice. The book will be written by a strong team at the University of Derby, with each contributor providing an expert voice on an area that they research and teach within. The range of chapters would make this a relevant title across the entire degree at both introductory and more advanced levels. The book's edge is its focus on debates taking place here and now, making the title urgent and relevant for students. It also encourages readers to think internationally"--